Integrasi Nilai-Nilai Ekonomi Syariah dalam Pengembangan Usaha Tembakau Rakyat: Strategi Pemberdayaan dan Ketahanan Ekonomi Petani - Mahali Andriyanto (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2026)
This study analyzes the integration of Islamic economic values into the development of smallholder tobacco farming as a strategy for farmer empowerment and household economic resilience in Pamekasan Regency, East Java, Indonesia. Using a descriptive qualitative case-study approach, the study draws on field observation, documentation, and secondary data from official statistics, regional agricultural records, regulatory documents, and recent literature on Islamic economics, Islamic microfinance, and Islamic social finance. The analysis focuses on five principles: justice, transparency, the prohibition of riba, the reduction of gharar, and the orientation toward maslahah. The findings show that the application of Islamic economic values can strengthen farmers’ bargaining position through transparent contracts, clearer quality standards, sharia-compliant financing, and productive use of Islamic social finance. Tobacco production in Pamekasan increased from 19,992 tons in 2023 to 28,296.7 tons in 2024, accompanied by the expansion of cultivated area from 22,304 to 31,183 hectares. Descriptive indicators also show an increase in monthly farmer income from IDR 1.2 million to IDR 1.8 million, wider access to Islamic financial services, and broader business diversification. The study concludes that Islamic economic values are not merely normative principles but can be operationalized as a governance framework for fairer rural value chains. However, the strategy must be implemented with strong ethical awareness, because the welfare of tobacco farmers should not be interpreted as the promotion of tobacco consumption.